Efeito sindêmico no risco para o HIV entre homens que fazem sexo com homens no Brasil - Araujo Junior, Antonio José Lima de (2022)
To characterize the effect syndemics conditions on HIV prevalence among men who have sex with men in Brazil. This is an excerpt from the research “National study of behaviors, attitudes, practices and prevalence of HIV, Syphilis and Hepatitis B and C among men who have sex with men”. Cross-sectional study, carried out between June and December 2016, in 12 Brazilian cities. The population consisted of MSM aged 18 years or over and who lived or studied in one of the participating cities. A national sample of 4,176 individuals was obtained, following the Respondent Driven Sampling (RDS) technique. For the classification of syndemics, the following criteria were considered: if there is the presence of two or more diseases or health conditions concentrated in a specific group; social factors that create conditions for two or more diseases or health conditions to be concentrated in a group; the concentration of these health conditions result in an adverse interaction of diseases with biological, social or behavioral elements. The Complex Analysis Survey tool in StataTR 14.0 was used with each city treated as its own stratum to weight the final results. There was a higher proportion of HIV positive results among MSM in the age group over 25 years (31.0%; 95%CI 25.6 – 37.0; p <0.001), with self reported sexual identity as bear/MSM/straight (23.2%, 95%CI 19.0 – 28.1; p <0.001), knowledge about PrEP (28.0%; 95%CI 21.5 – 35.7; p = 0.001), not having been tested for HIV and other STIs (24%; 95%CI 18.1 - 31.2; p<0.001). The presence of a health condition increases the chance of infection by the virus by 1.9 times (95%CI 1.1 – 3.2; p=0.009) and can reach 84.1 times in cases of 4 conditions present simultaneously (95%CI 7.1 – 99.0%; p<0.001). The syndemic (OR 1.7; 95%CI 1.1 – 2.8; p=0.017), age group ≥ 25 years (OR 3.2; 95%CI 2.0 – 5.1; p<0.001), unprotected anal sex (OR 2.0; 95%CI 1.1 – 3.8; p=0.021) knowledge about PrEP (OR 2.3; 95%CI 1.3 – 3.8; p=0.002) and sexual identity (OR 2.3 ; 95%CI 1.4 – 3.8; p=0.001) were associated with risk for HIV-positive results. There is a greater risk of HIV infection among MSM when associating syndemics with age over 25 years; knowledge about PrEP; receptive unprotected anal intercourse and sexual identity as understood, bear, MSM, or straight.